An Empirical Study on the Improvement of College Students’ Employability Based on University Factors - Zhang, Yi-Cheng; Zhang, Yang; Xiong, Xue-li; Liu, Jia-Bao; Zhai, Rong-Bing (Frontiers in Psychology, 2022)
With the popularization of higher education and the promotion of college enrollment expansion, the number of college graduates increase sharply. At the same time, the continuous transformation and upgrading of industrial structure puts forward higher requirements on the employability of college students, which leads to the imbalance between supply and demand in the labor market. The key to dealing with the employment difficulties lies in the improvement of college students' Employability. Therefore, we make a regression analysis of 263 valid samples from universities in Anhui Province, and extract the factors that influence the improvement of college students' employability in the process of talent cultivation in university. The result shows that there is a positive correlation between course setting, course teaching, club activities, and college students' employability, among which the course teaching and club activities are the most critical factors which may influence college students' employability. In addition, from the viewpoint of individual college students, the overall grades of college students and the time of participating in internship are also closely related to their employability, that is, college students with good overall grades and long internship time should also have stronger employability.